The Influence of Business Ethics, Service Quality and Brand Image on Customer Loyalty: Case Study at PT. Gojek Indonesia - Tesya Anggraeni Firdaus; Zandra Dwanita Widodo; Syahri Alhusin (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
In giving an image to a brand , people also assess business ethics and quality a company's services . People who have high taste in assessing business ethics will prioritize the quality of services provided by the company . If a business ethic that is considered good enough is accompanied by a company's social responsibility, then society will be more interested in providing a good attitude towards the company. The objectives of this research are as follows: 1) To determine the influence of business ethics on customer loyalty. 2) To determine the effect of service quality on customer loyalty. 3) To determine the effect of brand image on customer loyalty. This research was conducted at the PT. Gojek located in Solo . The subjects of this research are consumers of PT. Gojek/ The population in this research is Go-Jek users in the city of Solo. In this research, the sampling technique was carried out using probability sampling , namely random sampling . The sample used was 104 respondents who were Go-Jek users. The research results show that the variable business ethics shows a β coefficient of 0.237 at a significance level of 0.026. The service quality variable shows a β coefficient of 0.292 at a significance level of 0.000. The brand image variable shows a β coefficient of 0.292 at a significance level of 0.000. The Fcount value is 51.107 with a sig value of 0.000. Apart from that, it can also be seen that the calculated F value is 51.107 > F table 2.69, so it can be concluded that Ha is accepted and H0 is rejected . It can be concluded that business ethics, service quality and brand image have a positive and significant effect on customer loyalty.